Sustainable Development Goals The Impact of Sustainability Measures on Wellbeing - Sharma, Ridhima (Emerald Publishing Limited, 2024)
Sustainable Development Goalsintroduces the subject of sustainable development, delving into detail of the framework to address gaps and shortages in different disciplines and sectors. The global drivers of change are analysed and the opportunities and challenges of attainment of development goals are investigated
Description based on publisher supplied metadata and other sources
Keywords: Entwicklung; Nachhaltigkeit